Prostate Cancer Patterns and Trends in the Eastern Cape Province of South Africa; 1998–2017 - Ramaliba, Thendo Michael; Sithole, Nomfuneko; Ncinitwa, Akhona; Somdyala, Nontuthuzelo I. M. (Frontiers in Public Health, 2022)
Background Globally, prostate cancer is rated the second most common cancer and the sixth leading cause of death. In South Africa, it is ranked as leading cancer among men. This study describes prostate cancer patterns and trends in the rural Eastern Cape Province population. Methodology Secondary data were used from which a sample of 723 prostate cancer (C61) patients was extracted from the database into STATA version 14.0 for descriptive analysis. A direct standardization method was used to estimate age-specific and age-standardized incidence rates. Keyfitz method was used to calculate the standard error and confidence interval, whereas the Joinpoint program the annual percentage change. Results The mean age was 64 years, with a standard deviation of 9.9. Trends in prostate cancer incidence increased significantly (p = 0.026) from 7.4% in 2010 to 12.6% in 2017. Incidence rates varied across the region, with the lowest of 4.5 per 100,000 in 1998 to the highest of 21.4 per 100,000 in 2017 period. Lusikisiki had the highest incidence rates of 53.4 per 100,000 population (95% CI 0.8–61.4), while Centane with 21.7 per 100,000 (95% CI 2.3–27.6) rated the second. Other magisterial areas showed a constant increase (p > 0.05) throughout the observation period except for Idutywa and Willowvale, with no apparent increase. Conversely, in Butterworth, incidence rates decreased from 15.2 per 100 000 (95% CI 8.6–21.9) to 11.5 per 100,000 (95% CI 6.2–16.7). Conclusion As experienced globally and regionally, prostate cancer has become a public health concern in this population. Incidence variations across the surveillance area in the Eastern Cape were noted with hotspots.